Air Conditioner (AC) : dampak yang ditimbulkan terhadap efek gas rumah kaca: dampak yang ditimbulkan terhadap efek gas rumah kaca - Fuadati, Ifrokhatul (Maliki Interdisciplinary Journal, 2024)
AC is a device or machine that functions as an air conditioner. AC consists of several parts, including the compressor, condenser and evaporator. The function of the AC which absorbs hot air and releases it as cold air can provide comfort in the room. But on the other hand, AC has a bad impact because AC uses cooling materials that contain chlorofluorocarbons, which contribute to the greenhouse gas effect.